Heterosis and combining ability analysis for resistance to pod fly and lepidopteran borers in pigeonpea (Cajanus cajan) - LAL, S S; SINGH, I P; JEET, VISHWA (The Indian Journal of Agricultural Sciences, 2013)
A seven-parent diallel (without reciprocal) study was conducted during 1993-95 on the pod fly and lepidopteranborer damage to pigeonpea [Cajanlls cajan (L.) Millsp.) revealed that mean squares due to general and specific combiningability were significant but variance component due to sca was higher than variance component due to gca indicating thepredominance of non-additive gene action for inheritance of resislance to pod fly and lepidopteran borers. Parents 'PDA88-2E' and 'PDA 89-2E' were good combiners for pod fly resistance and 'ICP 8860' and 'Bahar' were the good combinersfor lepidopteran borer rersistance. The crosses 'NP(WR) 15' x 'PDA 88-2E', 'DPPA 85-15' x 'PDA 89-2E', 'NP(WR) 15'x 'PDA 89-2E', 'Bahar' x 'ICP 8860', 'DPIA 85-15' x 'PDA 88-2E' and 'Bahar' x 'PDA 88-2E' were found to be goodspecific combiner for resistance to pod fly and the cross 'KPBR 80-2-1' .x 'NP(WR) 15' was found to be a good specificcombiner for resistance to lepidopteran borer. Some of the crosses with high negative values showed high heteroticresponse over Mid Parent and Better Parent for resistance to pod fly and lepidopteran borer damage.